The effects of typical ageing on cognitive control: recent advances and future directions - Dexter, Melissa; Ossmy, Ori (Frontiers in Aging Neuroscience, 2023)
Cognitive control is one of the most fundamental aspects of human life. Its ageing is an important contemporary research area due to the needs of the growing ageing population, such as prolonged independence and quality of life. Traditional ageing research argued for a global decline in cognitive control with age, typically characterised by slowing processing speed and driven by changes in the frontal cortex. However, recent advances questioned this perspective by demonstrating high heterogeneity in the ageing data, domain-specific declines, activity changes in resting state networks, and increased functional connectivity. Moreover, improvements in neuroimaging techniques have enabled researchers to develop compensatory models of neural reorganisation that helps negate the effects of neural losses and promote cognitive control. In this article on typical ageing, we review recent behavioural and neural findings related to the decline in cognitive control among older adults. We begin by reviewing traditional perspectives and continue with how recent work challenged those perspectives. In the discussion section, we propose key areas of focus for future research in the field.